Journalism and Austerity : Digitization and Crisis During the Greek Memoranda - Kostopoulos, Christos (Digital Activism and Society: Politics, Economy and Culture in Network Communication Ser., 2020)
Using an original empirical study of the frame building process in the press, this book analyses the interplay between political economy and framing theories, focusing on what the frames found in the press can reveal about structural power struggles, and the contribution of journalism to democratic debate.